Evaluation of (GTG) 5-PCR for Genotyping of Klebsiella pneumonia Strains Isolated from Patients with Urinary Tract Infections - Reza RANJBAR; Davoud AFSHAR (Tehran University of Medical Sciences, 2019)
Background: Klebsiella pneumonia is one of the common causes of pneumonia and bacteremia in intensive care patients. The present study was aimed to determine the capability of (GTG) 5-PCR assay for molecular typing of K. pneumonia strains isolated from patients with urinary tract infections. Methods: In this descriptive-sectional study, K. pneumoniae strains were collected from hospitalized patients with urinary tract infection in Baqiyatallah Hospital, Tehran, Iran during 2017-2018. Isolates were identified by conventional microbiological tests. Bacterial DNA was extracted using boiling method and (GTG) 5-PCR assay was used for subtyping of the isolates. For clustering of isolates, dendrogram was generated according to the unweighted pair group method with arithmetic (UPGMA). Results: Overall, 88 K. pneumoniae isolates were isolated and subjected to the molecular typing study. The (GTG) 5-PCR assay was able to differentiate the K. pneumoniae strains into 9 clusters including G1-G9. Genotype clusters G4 and G9 consist of highest (26) and lowest (1) number isolate, respectively. Conclusion: The K. pneumonia strains isolated under the study belonged to various clones and the (GTG) 5-PCR assay as simple and rapid method can be a powerful tool for molecular typing of K. pneumoniae strains.